1999
DOI: 10.1007/bf02481744
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis-induced coronary constriction in the rat heart: Evidence for the activation of L-type calcium channels

Abstract: Perfused rat hearts were used to study the effects of acidosis on coronary tone. When pH was decreased, over the range pH 7.4 to pH 6.2, by reducing perfusate bicarbonate levels, under constant flow conditions, there was a transient decrease in coronary perfusion pressure (CPP), followed by a sustained acidosis-dependent increase in CPP, which reversed when pH was returned to pH 7.4. This increase in CPP was seen at perfusion rates of 5, 10, and 20 ml/min(-1). When using constant pressure perfusion acidosis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 28 publications
2
12
1
Order By: Relevance
“…Changing the pH of the perfusate from 7.4 to alkaline pH resulted in an increase of coronary perfusion pressure in both WKY and SHR, confirming previous reports (5,19). However, effects of acidic pH on coronary arteries in normotensive rats have been controversial (8,18). Moreover, previous reports paid no attention to the blood pressure in rats.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Changing the pH of the perfusate from 7.4 to alkaline pH resulted in an increase of coronary perfusion pressure in both WKY and SHR, confirming previous reports (5,19). However, effects of acidic pH on coronary arteries in normotensive rats have been controversial (8,18). Moreover, previous reports paid no attention to the blood pressure in rats.…”
Section: Discussionsupporting
confidence: 74%
“…However, previous reports were controversial. While, it was reported that acidosis caused vasodilation in coronary arteries of the Sprague-Dawley rat (8), pig (15,16), and dog (17), Wilson and Woodward (18) reported that acidosis induced coronary constriction in the rat heart. The animals used in these reports were all normotensive, and the effect of acidosis on coronary arteries in hypertensive animals was not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…2 What makes the disparity in the 2 models more substantial is the evidence in literature that acidosis had induced contraction of VSM in other rodent models as well. 6 A direct implication of VSM K ϩ ATP channels has been elucidated in control of vasculature tone in an isolated study by Wang et al on rodent vasculature as well. Therefore, we cannot disregard the fact that the study was on mesenteric vasculature and the results cannot be generalized to coronary vasculature.…”
Section: To the Editormentioning
confidence: 99%
“…On the contrary, it was also reported that acidosis decreased coronary blood flow in anaesthetized dogs (Goodyer et al . ), increased coronary perfusion pressure (vasoconstriction) in rat isolated heart (Wilson & Woodward, ) and contracted RCA in both wire‐mounted rings and cannulated isolated RCA segments (Baxter et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…; Lindauer et al . ), L‐type voltage‐gated Ca 2+ channels (LVGCs; Wilson & Woodward, ), ATP‐sensitive K + (K ATP ) channels (Ishizaka & Kuo, ), nitric oxide (Celotto et al . ) and prostanoids (Celotto et al .…”
Section: Introductionmentioning
confidence: 99%